Off seasonal and pre-seasonal assessment of circulating energy sources during prolonged running at the anaerobic threshold in competitive triathletes - Knoepfli, B.; Riddell, M. C.; Ganzoni, E.; Burki, A.; Villiger, B.; von Duvillard, S. P. (British Journal of Sports Medicine, 2004)
Objectives: To compare changes in circulating energy sources during prolonged exercise in off season (OS) and pre-season (PS) training of triathletes.